The Fall of Global Socialism A Counter-Narrative From the South - Jayatilleka, D. (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
This radical new perspective from the Global South casts a fresh light on a major aspect of contemporary history and in doing so suggests an alternative interpretation of twentieth century revolutions, Socialism, left thinking and radical politics.